Siederella Szlach. & al. and Irenea Szlach. & al. - new genera of the tribe Oncidieae (Orchidaceae) - Szlachetko, Dariusz L.; Mytnik-Ejsmont, Joanna; Górniak, Marcin; Romowicz, Agnieszka (Biodiversity: Research and Conservation, 2006)
Two new Neotropical orchid genera - Siederella Szlach., Mytnik, Górniak & Romowicz, gen. nov. and Irenea Szlach., Mytnik, Górniak & Romowicz, gen. nov. - of the tribe Oncidieae (Vandoideae, Orchidaceae) are described. Taxonomic affinities of the newly proposed taxa are briefly discussed. New nomenclatorial combinations are proposed.